Enhancing Teachers’ Professional Development for Supporting Special Needs Students with Speech Delays and Cognitive Difficulties in Inclusive Early Elementary Classrooms - Noor, Rifat E (International Journal of Rehabilitation and Special Education (IJRSE), 2026)
This study explored how professional development (PD) programs prepare general  and special education teachers to manage speech delays and cognitive difficulties  among students in inclusive early elementary classrooms. A qualitative research  approach was employed using semi-structured interviews, focus group discussions,  and classroom observations conducted within an urban school system. Participants  included special education teachers and regular classroom teachers working with  students from pre-kindergarten to grade two. The findings revealed major barriers  related to communication difficulties, limited differentiated instructional strategies,  inadequate professional development opportunities, and challenges associated with  inclusive classroom management. Teachers emphasized the importance of visual  aids, collaborative learning, individualized support, and continuous communication  between educators and parents. The study also identified gaps in teacher training  and resource availability, particularly for novice teachers. The results suggest that  structured and practical professional development programs can significantly improve  teaching effectiveness and support positive educational outcomes for students with  developmental delays. The study contributes to the field of inclusive education by  offering practical recommendations for schools, policymakers, and teacher-training  institutions to improve inclusive learning environments.
Keywords: Inclusive education, professional development, speech delay, cognitive difficulties, special education, teaching strategies